Modified hematological sepsis score: an easy and cost effective measure to combat neonatal septicemia - Varughese, Pearl Mary (International Journal of Research in Medical Sciences, 2020)
Background: Early diagnosis of neonatal sepsis continues to be a problem because of subtle and non-specific clinical features. Blood culture is the gold standard, but it takes several days and is expensive. The hematological scoring system (HSS) consisting of different blood parameters could be an effective and simple method to help diagnose and treat neonatal sepsis. Aim of the present study was undertaken to highlight the importance of HSS in the early diagnosis and evaluation of neonatal septicaemia. Methods: This was a prospective study done in a peripheral hospital in Kerala. The inclusion criteria involved all inborn babies above 34weeks gestation. Exclusion criteria involved babies with congenital anomalies, congenital heart diseases, pathological jaundice, birth weight less than 2kg and babies requiring NICU admission, 550 babies were included in the study. Cord CRP and 48 hours CRP was taken. At 48 hours, blood samples were also taken for Total count (TC), Absolute Neutrophil Count (ANC), Platelet count, and peripheral smear. Blood culture was taken for babies suspected to have sepsis and started on antibiotics. The screening parameters were assessed for individual performance and in combination. Results: Individually, though parameters like TC, ANC, 48 hrs CRP and platelet count had excellent sensitivity (100%) and NPV (100%), their specificity was low 65%-82%. Degenerative changes showed sensitivity 94.1%, specificity 91% and NPV 99.8%. HSS score >5 and >6 had better specificity and NPV. Conclusions: HSS scoring can be used to safely exclude neonatal sepsis, thus avoiding unnecessary antibiotic exposure in newborns and undue worry for parents.